A study on "five-year program for veterinary services" - Ayşe Menteş Gürler (Eurasian Journal of Veterinary Sciences)
livestock. all over the world. need to be developed at nationallevel is considered as a strategic seeter. Especially due to epidemic diseases which becomes more important in war conditions, veterinary medicine service was conducted by "UmOr-u Baytarlye Department" which was established 14 June 1920 in Ankara . during the War of Independence. After the declaration of the Republic , ızmir Economy Congress was collected in 1923. As a part of decisions taken in this Congress in the framework of veterinary services with the aim of the reorganization , "Five Year Program for Veterinary Service s" was prepared in 1924. Specified in the program between objecti ves , improvement of animal breeds and reproduction , yield enhancement of the product to evaluate, parks , markets, fairs and other places to encouraging manufacturers to create environment, epidemic disease prevention , adequate and competent staffto bring up issues such as are available.